Integrating whole trait theory and self‐determination theory. Issue 1 (14th August 2018) - Prentice, Mike; Jayawickreme, Eranda; Fleeson, William
Abstract: We explore and explicate some promising points of integration between self‐determination theory (SDT) and whole trait theory (WTT). Integrating SDT and WTT can offer an example for navigating challenges that have long confronted integrating trait‐descriptive and motivational‐explanatory views of personality. We review SDT and WTT in turn. The review of SDT is organized around the emergence of its six mini‐theories. The review of WTT will introduce the descriptive and explanatory elements as aspects of whole traits, and it will also provide a functional view of traits as tools for goal pursuit. For integrating the two, we point out the many instances in which SDT motivational concepts are interpretive or goal activation processes that act as intermediaries between the inputs and outputs WTT describes. Because WTT has focused on outputs as trait manifestations, we can begin to link SDT's need satisfaction processes to traits and their manifestations. This integration leads to a key proposition that traits are tools for satisfying basic psychological needs ; basic psychological needs can (partially) explain traits. This then paves the way to novel research questions.